Detecting pyrethroid resistance in predatory mites inhabiting soil and litter: an in vitro test. Issue 6 (27th December 2016) - El Adouzi, Marine; Bonato, Olivier; Roy, Lise
Abstract: BACKGROUND: While resistance against insecticides is widely known in pest arthropods, it remains poorly known in non‐target arthropods of the same agrosystems. This may be of crucial importance in the context of organic pest management or integrated pest management. First, stopping of pesticide pressure during farm conversion may lead to important rearrangements of non‐target communities due to fitness cost of resistance in populations of some species. Second, resistant biological agents may be useful to farms with low synthetic pesticide use. Communities of mesostigmatid mites, encompassing numerous predatory species, are supposed to be involved in important ecological processes in both crop soils and animal litter/manure. RESULTS: Here we provide a tarsal contact method for assessing resistance in different populations from various species of mesostigmatid mites. Analyses of data from repeated tests on three populations from different mesostigmatid families proved the method to be robust and able to generate consistent and reliable mortality percentages according to insecticide concentration. CONCLUSION: Our bioassay system allows for both one‐shot estimate of pyrethroid sensitivity in mite populations and estimation of how it changes over time, making possible survival analyses and assessment of recovery from knockdown. The rating system retained makes it possible to score response to insecticides in a consistent and standard way in species from different mesostigmatid families. © 2016 Society of Chemical Industry